"It makes such a difference": An examination of how LGBTQ youth talk about personal gender pronouns. Issue 1 (January 2020) - Brown, Camille; Frohard-Dourlent, Hélène; Wood, Brittany A.; Saewyc, Elizabeth; Eisenberg, Marla E.; Porta, Carolyn M.
ABSTRACT: Background and purpose: The World Health Organization has developed standards for youth-friendly health services to support adolescents and encourage health care utilization among youth. Necessary building blocks for youth-friendly care include strong interpersonal relationships between youth and health care providers. Nurse practitioners (NPs) may be particularly well positioned to form these relationships. This study explored a core aspect for building youth–provider relationships. The study examined how lesbian, gay, bisexual, transgender, and queer (LGBTQ) adolescents discussed use of personal pronouns (e.g., he, she, they, ze) in relation to transgender and gender diverse (TGD) people. Methods: A secondary qualitative analysis of 66 in-depth interviews with LGBTQ youth from across Minnesota, Massachusetts, and British Columbia, Canada was conducted. Results were sorted into four main themes describing different aspects of personal pronoun use as related to TGD individuals. Conclusions: Stories and experiences shared by participants illustrate how to assess which pronouns to use for a given person, how to use pronouns in different contexts, why respecting pronouns is important to TGD people, and flexibility as an integral component of the learning process when it comes to appropriate pronoun use. Implications for practice: Understanding how youth discuss personal pronouns could improve practice with TGD youth. Each of the four themes can be applied to clinical encounters to ensure culturally sensitive care. Practice recommendations include asking adolescents what pronouns they prefer clinic staff to use on intake forms and having NPs and clinic staff provide their own pronouns to patients in introductions.